Working While Ill Is Not Always Bad—Positive Effects of Presenteeism - Lohaus, Daniela; Habermann, Wolfgang; El Kertoubi, Isam; Röser, Florian (Frontiers in Psychology, 2021)
Presenteeism – going to work while ill – is a widespread phenomenon worldwide. Previous research has concentrated mainly on its negative effects. This study investigates the positive consequences of presenteeism derived from a comprehensive content model of presenteeism that was developed on the basis of negative effects. In a quantitative online-survey employees (N=181) rated the degree of experienced or potential positive effects depending on whether they had worked while ill (75%) or not (25%) during the previous year. Results revealed that all postulated positive effects described in the content model were relevant. Most positive effects were rated significantly higher by participants who had shown presenteeism in comparison to those who had not. The positive effects significantly predicted presenteeism propensity (adjusted R2 = .20) for participants having shown presenteeism. In addition, an overall rating of positive effects was significantly related to presenteeism, however, to a lesser degree. Overall, the results demonstrate the applicability of the content model to positive effects of presenteeism. They point to the need for further investigation of them and their consideration for the management of presenteeism.